Sustainability of pepper cultivation in Lampung, Indonesia, with rap-pepper coordination techniques and pepper thresher technology - Umihanni, Elvira; Haryono, Dwi; Murniati, Ktut; Endaryanto, Teguh (Edelweiss Applied Science and Technology, 2026)
This study evaluates the sustainability of pepper cultivation in Lampung, Indonesia, using the Rap-Pepper multidimensional scaling (MDS) method and pepper threshing technology. Pepper is a strategic commodity, yet its sustainability faces challenges from declining productivity and post-harvest inefficiency. This research employs quantitative and qualitative methods, assessing five dimensions: ecological, economic, social, technological, and institutional. A pepper threshing tool was also designed and tested to improve processing efficiency. Results indicate a sustainability index of 64.95, categorized as "quite sustainable," with technological and institutional dimensions identified as the weakest aspects. The threshing equipment increased harvest efficiency by 40% and reduced seed damage by 15% compared to manual methods. Findings suggest that while technological innovation provides solutions, limited training and institutional support hinder widespread adoption. A significant policy model for increasing the index involves productivity-focused approaches, such as providing disease-resistant seedlings. The study concludes that sustainable development requires active government and private involvement to strengthen farmer capacity through education and incentives. These results serve as a reference for stakeholders to design strategies based on technological innovation and institutional strengthening to enhance productivity and farmer welfare.